New species of the genus Eupithecia (Lepidoptera, Geometridae) from China. Part VII - Mironov, Vladimir; Šumpich, Jan (Zootaxa, 2022)
In this seventh part of this series, 8 new species of Eupithecia Curtis, 1825 are described from China: Eupithecia prochazkai sp. n., Eupithecia anickae sp. n., Eupithecia divertenta sp. n., Eupithecia saldaitisi sp. n., Eupithecia ludificata sp. n., Eupithecia butvilai sp. n., Eupithecia ursina sp. n. and Eupithecia nesciaria sp. n. Three previously described species are recorded in China for the first time: Eupithecia oxycedrata (Rambur, 1833), Eupithecia phulchokiana Herbulot, 1984, and a range extension is given for a fourth, Eupithecia pannosa Mironov & Galsworthy, 2008, and Eupithecia matrona Mironov & Galsworthy, 2004. Adults and genitalia are illustrated for all species.